Perturbações do Comportamento Alimentar e Covid19 - Marta Cristina Faria Silva (2022)
The impacts of COVID19 on patients with a history of eating disorders have been extensively studied worldwide. However, more robust evidence emerges from the American and European continents. The aim of this work is to describe the changes and effects that the pandemic caused in the continents of Europe and America in patients with and at risk of Eating Disorders (ED). For this, some factors were investigated, such as 1) symptoms related to eating disorders (either general or specific), 2) the impact on depressive symptoms and anxiety, 3) excessive physical exercise or the need to restrict it and 4 ) the effect of tele-therapy and restrictions on face-to-face treatment. In general, there was a worsening of symptoms related to eating disorders and an increase in depressive symptoms and anxiety. However, studies show variability in the practice of physical exercise or the need to restrict it, as well as a duality in what is the effect of tele-therapy. The changes that occur in this theme in the continents of Europe and America are similar.